Industrialization in fisheries: a challenge to change - Achmad Poernomo; Endang Sri Heruwati (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2011)
To manage with the Indonesian vision as the biggest producer of fisheries in 2015, capture,aquaculture, and post-harvest fisheries should be ready to operate at large or business scale.Consequently, industrialization should be promoted since this is the most appropriate way tomanage fisheries in business manner. Though it has a positive goal to maximize the utilization offisheries resource for the improvement of economic and prosperity of Indonesian people, however,industrialization undoubtedly retains a negative impact in terms of threats on the sustainability offishery and other natural resources. This article summarises review and analysis aiming to developan ideal model in order to strengthen the fisheries industrialization in Indonesia. Based on previousweaknesses, the ideal model is the one that reflects an inclusive and holistic manner, suitable forvarious characteristics of industries in each typical areas and people of Indonesia, with the emphasison competitive advantage, untraditional, and commercial basis, especially in respect to thedevelopment of a strong fisheries business. This kind of model should also maintain harmonizedand coordinated programs and actions between involved related institutions. Research supportsare needed to develop and test the most appropriate model. Also, in technical basis, innovationson fish capture, aquaculture, as well as processing technologies are urgently needed as acomplement to the developed model of fisheries industries. One thing that should be kept in mindis the importance of management and conservation of natural resources, including resource forfisheries capture and aquaculture, germ plasms and genetic fish resources, as well as marinemicroorganisms, as these all are the main assets for the development of marine and fisheries inIndonesia.